The role of compassion in shaping social entrepreneurs’ prosocial opportunity recognition - Yitshaki, Ronit (Journal of business ethics, 2022)
Compassion is acknowledged as a key motivational source of prosocial opportunity recognition (OR). This study examines the underlying processes of different types of compassion that lead to prosocial OR interventions designed to solve or ameliorate social problems. Self-compassion is associated with intimate personal experiences of suffering and encompasses a desire to alleviate the distress of others based on common humanity, mental distance and mindfulness. Other-regarding compassion is associated with value structures and social awareness and is based on a desire to help the less fortunate. Using a life-story analyses of 27 Israeli social entrepreneurs, we identified two OR process mechanisms, reflexivity (identifying overlooked social problems) and imprinting (identifying a known social problem within the social context). The relationship between these two types of compassion are equifinal, that is, both can lead to prosocial OR; however, the mechanisms differ. We contribute to the literature by showing that compassion serves as an internal enabler based on both cognitive and affective motivations for prosocial OR. We introduce a theoretical perspective that establishes a process model for further research on the role of compassion in identifying and leading prosocial action.